Protection of traditional knowledge, an incomplete victory, towards inclusion of gender considerations in traditional knowledge protection: a Zambian perspective - Sinkala, Ruth Mulenga (Department of Commercial Law, 2023)
This thesis explores the important issue of protection of traditional knowledge from a gendered perspective. More specifically, it seeks to explore the traditional knowledge protection landscape in Zambia in the context of gender sensitivity and gender responsiveness. It further delves into the role of gender considerations in traditional knowledge protection in the achievement of Zambia's national and international development goals. The work relies on desktop research. It draws on primary and secondary sources of information to inform the analysis, provide the necessary background to ground and situate the research. This thesis argues that a gendered approach to TK protection is justified and important. Based on analysis of the prevailing traditional knowledge protection regime in Zambia, the thesis finds and contends that the current protection available is neither gender sensitive nor gender responsive. Further, the current traditional knowledge protection provided in Zambian legislation falls short in various aspects. The role of gender sensitive and gender responsive traditional knowledge protection in the achievement of Zambia's national and international development objectives as expressed in the Zambian Vision 2030 and Sustainable Development Goals is also explored in the work. This thesis suggests that Zambia's traditional knowledge protection regime must be changed to include gender considerations. It presents recommendations for change for Zambia from a legislative perspective partially based on emulating the traditional knowledge protection strategy adopted in Kenya. Gender considerations in traditional knowledge protection legislation in Zambia must be included to ensure that protection is real and effective for women. Through this work it is hoped that attention is drawn to the urgent need for decisive changes in the traditional knowledge protection regime in Zambia in the context of gender sensitivity and gender responsiveness.